Implementation of SEIP (Spiritual, Emotional Intellectual and Physical) Method in Learning for Students in Junior High Schools - Mendrofa, Kristiana; Lay, Sergius; Harefa, Tetinia (Jurnal Pendidikan Non formal, 2024)
This study aims to determine what the SEIP method means and how teachers apply it in learning for students in junior high schools. This study applies a literature study method through the collection of library sources to obtain research data. Library data collection is limited to library collection materials only without requiring field research. In this case, the author collects relevant reference sources, such as books, documents, the Indonesian dictionary, and so on. Literature search with the keywords "Implementation", "SEIP Method (Spiritual Emotional Intellectual and Physique)", and "Junior High School". The results of the study show that the SEIP method is a consequence of awareness of self-authenticity and activates the four intelligences inherent in each individual. One way for teachers to be able to carry out this task is to develop strategies and methods used in delivering lesson materials. The SEIP method is one method that can be used by teachers so that learning materials can be digested and understood by students so that the learning process becomes more active and creative.